2014
DOI: 10.1016/j.healun.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

T-regulatory cell treatment prevents chronic rejection of heart allografts in a murine mixed chimerism model

Abstract: BackgroundThe mixed chimerism approach induces donor-specific tolerance in both pre-clinical models and clinical pilot trials. However, chronic rejection of heart allografts and acute rejection of skin allografts were observed in some chimeric animals despite persistent hematopoietic chimerism and tolerance toward donor antigens in vitro. We tested whether additional cell therapy with regulatory T cells (Tregs) is able to induce full immunologic tolerance and prevent chronic rejection.MethodsWe recently develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 32 publications
2
60
0
Order By: Relevance
“…Relatively low chimerism levels were observed with this protocol, but transplantation of BM retrieved from chimeras into secondary BMT recipients demonstrated that HSC engraftment had been achieved in the primary BMT recipients [40]. Donor skin and heart transplants were shown to be permanently accepted (while third party grafts are rejected) and in vitro assays demonstrated donor-specific T-and B-cell tolerance in the recipients [40,41]. Several types of tested recipient Treg cells (i.e., FoxP3-transduced, activated Treg cells and TGF-β-induced Treg cells) were shown to be effective in this setting [40] with recipient Treg cells being more potent in inducing chimerism than donor or third party Treg cells (unpublished data).…”
Section: Noncytoreductive Conditioning Protocolsmentioning
confidence: 95%
See 4 more Smart Citations
“…Relatively low chimerism levels were observed with this protocol, but transplantation of BM retrieved from chimeras into secondary BMT recipients demonstrated that HSC engraftment had been achieved in the primary BMT recipients [40]. Donor skin and heart transplants were shown to be permanently accepted (while third party grafts are rejected) and in vitro assays demonstrated donor-specific T-and B-cell tolerance in the recipients [40,41]. Several types of tested recipient Treg cells (i.e., FoxP3-transduced, activated Treg cells and TGF-β-induced Treg cells) were shown to be effective in this setting [40] with recipient Treg cells being more potent in inducing chimerism than donor or third party Treg cells (unpublished data).…”
Section: Noncytoreductive Conditioning Protocolsmentioning
confidence: 95%
“…Along these lines, regulation is critical in the NHP setting and in clinical trials (see below) in which permanent mixed chimerism (which is a prerequisite for maintaining continuous central deletion) is not achieved [69]. Combining Treg-cell therapy with noncytoreductive BMT actively has been shown to potentiate regulatory mechanisms [40,41]. Clonal deletion has been shown with such a Treg-cell chimerism regimen, but is less pronounced, while regulation is predominant throughout follow up.…”
Section: Regulatory Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations